Penguatan Asas-Asas Hukum dalam Legislasi Limpahan melalui Pendekatan E-Democracy Berbasis Teknologi Digital - Muhammad Fauzan Arjuna; Raditya Wardana; Juliandro Meko Bimantara; Muhammad Gibrand Riverno; Falah Andhesryo (VJJ, 2023)
Delegated legislation plays a vital role in Indonesia's legal framework, serving as a tool for detailing core statutory norms through technical regulations. However, the implementation of delegated legislation in Indonesia is often considered ineffective. This is due to a lack of transparency, limited public participation, and inadequate oversight mechanisms for officials delegated authority. There are cases where implementing regulations even exceed the authority established by law, ultimately threatening legal certainty. Given the rapid development of digital technology, the concept of e-democracy (electronic democracy) offers an innovative solution. This approach aims to strengthen legal principles in delegated legislation through digital transparency practices, online public consultations, and the use of advanced technologies such as artificial intelligence and blockchain. This article outlines how adopting this digital approach can substantially improve the quality of delegated legislation and strengthen the principles of legality, openness, accountability, and legal certainty. This document also emphasizes that close collaboration between the disciplines of law and computer engineering is an absolute prerequisite for creating an effective e-legislation model that is able to respond to the needs of society. Keywords: Delegative Legislation; Electronic Democracy; Legal Principles; Digital Governance; Drafting Of Legislation